Researches on suppliers selection based on improved AHP-TOPSIS method - Wang, Xinchen; Ma, Yanhua; Gao, Pengfei; Zhai, Lu; Gu, Bing (IOP conference series. Materials Science and Engineering, 2020)
Selection of supplier can be considered as the significant strategic decision for company's competitive advantage. Generally, the scales of criteria for selection were used to evaluate the performance of suppliers. But the traditional criteria are limited to reflect the comprehensive ability of the suppliers. Meanwhile, the quantitative scale, which is used to evaluate the suppliers, is too subjective to describe the real station of suppliers. Therefore, the improved analytic hierarchy process (AHP) is conducted to reanalyze the criteria and distribute the weight for each criterion. Technical for order preference by similarity to ideal solution (TOPSIS) used to calculate the relative proximity for each supplier and rank them based on the corresponding information. Finally, the calculate process is programmed by Excel VBA and MATLAB respectively. The two results show the same ranking order, which verify the improved AHP-TOPSIS method can effectively guide company to select supplier.